Biological Nitrogen Fixation and Denitrification in Rhizosphere of Potato Plants in Response to the Fertilization and Inoculation - Volkogon, Vitaliy V.; Dimova, Svitlana B.; Volkogon, Kateryna I.; Sidorenko, Vasyl P.; Volkogon, Mykola V. (Frontiers in Sustainable Food Systems, 2021)
The study aim was to evaluate the potential nitrogen fixation and denitrification in the rhizosphere soil of potato plants, crop yield and output quality in response to the different fertilization systems and the inoculation with Azospirillum brasilense 410. Field stationary experiment was conducted between 2016 – 2019 with potato in a crop rotation system on leached chernozem soil. Farmyard manure, 40 t/ha, applied prior to potatoes planting promotes nitrogen fixation (0.8 – 2.0 times compared to control). However, it has also affected denitrification (in 1.4 – 2.2 times higher compared to control). The lowest rate of mineral fertilizers used in the experiment, N40P40K40, was shown as most environmentally feasible. Under its use the increase of soil nitrogenase activity and low denitrification levels were observed. Same trends were also noted for the medium fertilizer rate, N80P80K80. The highest doses of mineral fertilizers, N120P120K120, substantially affected the denitrification process and reduced the nitrogen fixation activity (1.9 – 2.2 times). The combination of manure with the medium fertilizers rate has also resulted in high denitrification levels, while the soil nitrogen fixation activity has restored only at flowering stage. Crop inoculation with A. brasilense combined with the manure application, has not affected studied processes. However, crop inoculation after the green manure intercropping has shown the growth of nitrogenase activity. On mineral fertilizers background inoculation has activated nitrogen fixation and has ensured the decrease of denitrification levels, subject to the fertilization background. High fertilizer rates have hampered the inoculation efficiency. Inoculation has promoted crop yields on unfertilized and mineral backgrounds or following green manure. Crop inoculation following organic and the organo-mineral backgrounds had no significant effect, probably due to the competition from microorganisms that have created a competitive environment for A. brasilense. Despite its environmental expediency, inoculation combined with the low fertilizer doses underperforms the action of inoculation combined with the medium fertilizer rates showing the latter as the compromise between the environmental requirements and crop productivity. The use of inoculation has promoted the accumulation of starch and ascorbic acid and has contributed to the reduction of nitrate contents in the tubers of inoculated plants.